Effect of Lactate Minimum Speed-Guided Training on the Fluid, Electrolyte and Acid-Base Status of Horses - Titotto, Angélica C. [UNESP] (2023)
The effect of lactate minimum speed (LMS)-guided training on horses’ homeostasis is still unknown. Thus, this study aimed to evaluate the effect of an LMS-guided training program on the fluid, electrolyte and acid-base status of horses. Ten untrained Arabian horses were submitted to an LMS test on a treadmill before and after six weeks of training. The training intensity was 80% of the LMS in the first three sessions and 100% of the LMS in the other sessions. The venous blood was collected before (T-1) and after (T-2) training at rest, during and after the LMS test for lactate, pH, pCO2, HCO3−, and electrolyte measurements. The LMS and strong ion difference (SID4) were calculated. A mild increase in the mean values (p > 0.05) was observed at rest in T-2 in comparison with T-1 in the following variables: pH (from 7.436 ± 0.013 to 7.460 ± 0.012), pCO2 (from 42.95 ± 1.58 to 45.06 ± 0.81 mmHg), HCO3− (from 27.01 ± 1.02 to 28.91 ± 0.86 mmol/L), and SID4 (from 33.42 ± 1.45 to 35.06 ± 2.94 mmol/L). During T-2, these variables were more stable than during T-1. Despite the improvement in fitness, the LMS did not indicate a significant difference (from 5.40 ± 0.55 to 5.52 ± 0.20 m/s). The results confirmed that the LMS-guided training program had a positive impact on the horses’ acid-base status, although some adaptations are still required to improve their fitness.